Fenología y ecotisiología de dos poblaciones de Tabebuia rosea ("Roble de Sabana") en Costa Rica (Bignoniaceae) - Gómez Figueroa, Patricia (1996)
Leaf flushing, leaf fall, flowering and fruiting were observed during a period of tbree years in a population of 32 trees of Tabebuia rosea in San Pedro de Montes de Oca (120 0 masl) and Santa Ana (909 masl). These four phenological characteristics showed a strong periodicity. Leaf fall is more pronounced during dry season, favored by high temperatures and drought. Shoot growth is more einphasized during the wet season and is related to high temperatures. A positive correlation was determined between shoot growth, rain fall and high temperatures, but in the case of leaf fall and the rain fall the correlation was negative. The flowering season needs a high thermal oscilation and a dry period. Similarly, fruiting occurs during the dry season and lasts more than flowering.